2020
DOI: 10.1038/s41420-020-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 derived from cancer-associated fibroblasts attenuates the p53 response to doxorubicin in prostate cancer cells

Abstract: Cancer-associated fibroblasts (CAFs) promote tumor growth and progression, and increase drug resistance through several mechanisms. We have investigated the effect of CAFs on the p53 response to doxorubicin in prostate cancer cells. We show that CAFs produce interleukin-6 (IL-6), and that IL-6 attenuates p53 induction and upregulation of the pro-apoptotic p53 target Bax upon treatment with doxorubicin. This is associated with increased levels of MDM2 mRNA, Mdm2 protein bound to p53, and ubiquitinated p53. IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 64 publications
2
50
0
1
Order By: Relevance
“…Moreover, experimental models with CAFs isolated from bone metastases illuminated a role of oncogenic miR-221-containing CAFs microvesicles in inducing hormonal therapy resistance in human BrCa cells, a mechanism that was mainly sustained by autocrine IL-6 signaling [ 137 ]. CAFs-derived IL-6 was further shown to mediate resistance to the cytotoxic effects of doxorubicin in PrCa cells [ 138 ]. These observations may identify CAFs as a promising target in bone-homing malignancies.…”
Section: Impact Of Inflammation On Cancer Metastases To Bonementioning
confidence: 99%
“…Moreover, experimental models with CAFs isolated from bone metastases illuminated a role of oncogenic miR-221-containing CAFs microvesicles in inducing hormonal therapy resistance in human BrCa cells, a mechanism that was mainly sustained by autocrine IL-6 signaling [ 137 ]. CAFs-derived IL-6 was further shown to mediate resistance to the cytotoxic effects of doxorubicin in PrCa cells [ 138 ]. These observations may identify CAFs as a promising target in bone-homing malignancies.…”
Section: Impact Of Inflammation On Cancer Metastases To Bonementioning
confidence: 99%
“…Consistently, the activity of the IL-6/STAT3 signaling pathway is proportional to the growth rate of advanced prostate cancer [ 56 ]. Additionally, it has been found that in LNCAP cells the IL-6-activated JAK/STAT3 pathway also downregulates p53, a major cell cycle regulator [ 57 , 58 ]. Multiple lines of evidence indicate that the CAF-secreted IL-6 may also influence tumor growth by affecting AR activity.…”
Section: Rsv Inhibits Prostate Cancer Cell Proliferation By Targetmentioning
confidence: 99%
“…Studies showed that altered p53 function in CAFs contributes to tumor progression 20 . Another study showed that IL-6 secreted from CAFs depletes p53 through STAT3 in prostate cancer cells 21 . Therefore, CAFs serve as a powerful partner for cancer cells, enabling the latter to invade and metastasize to many sites.…”
Section: Effect Of Cdes On Cafsmentioning
confidence: 99%